Dynamics of macronutrient uptake and removal by modern peanut cultivars - Crusciol, Carlos Alexandre Costa [UNESP]; Portugal, José Roberto [UNESP]; Bossolani, João William [UNESP]; Moretti, Luiz Gustavo [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Garcia, Jader Luis Nantes [UNESP]; Garcia, Gleize Leviski de Brito [UNESP]; Pilon, Cristiane; Cantarella, Heitor (MDPI, 2021)
The productive potential of new peanut cultivars has increased over the years in relation to old cultivars, especially when compared with ones with upright growth habit. Thus, the requirement for macronutrients for these new cultivars may also have increased, making the existing fertilizer recommendation tables obsolete, thus increasing the need for further studies measuring the real macronutrient requirements of these new peanut cultivars. Our study aimed to evaluate the growth patterns and the macronutrient absorption rate throughout the biological cycle of three modern runner peanut cultivars, as well as the potential for producing dry matter, pods, and kernels, and their respective macronutrient accumulations. The experimental design was a randomized complete block with split-plots and nine replications. The experimental plots consisted of three peanut cultivars (IAC Runner 886, IAC 505, and IAC OL3), and subplots consisted of nine plant samplings (14, 28, 42, 56, 70, 84, 105, 126, and 147 days after emergence (DAE)). Our results showed that modern peanut cultivars presented nutrient accumulation around 30 to 40 days earlier than older cultivars, as well as increasing the uptake by K and Ca. IAC 505 absorbed higher amounts of macronutrients and resulted in greater dry matter production compared with IAC OL3 and IAC Runner 886. Our study demonstrated that the most appropriate time for plants to find greater availability of nutrients in the soil is 70 to 84 DAE, in addition to highlighting the need for updates on nutritional recommendations for higher yields of modern peanut cultivars.
Keywords: Arachis hypogaea L; Mineral absorption; Plant growth; Plant nutrition